Handbook of systems and complexity in health - Martin, Carmel M.; Sturmberg, Joachim P. (Springer New York, 2013)
Systems and complexity theory plays critical roles in such varied fields as computer science, the physical sciences, meteorology, and economics--and yet health care has yet to take full advantage of what it has to offer. What the theory offers is on rich display as the Handbook of Systems and Complexity in Health presents a revolutionary approach to reforming basic practice and large-scale care delivery, based on the concept of health care as a complex, self-organized, and self-interactive system.   The book's opening section provides readers with a thorough grounding in systems and complexity theory from scientific, historical, epistemological, and technical perspectives, complete with the principles and mathematics behind it. From there, contributors offer models of innovation and improvement in service delivery, disease prevention and health promotion, cost-effectiveness, communication, quality control--in short, a more efficient and equitable future for health care. And one particularly intriguing chapter suggests opportunities for complexity theory in refining the drug prescription process. A sampling of the coverage:   Understanding health and illness from a complexity perspective. A methodology for analyzing medical data. Modeling illness and recovery with nonlinear dynamics. Clinical applications: inflammation, diabetes, panic disorder, pain, domestic violence, cardiovascular disorders, and the art of the consultation. Complexity science at the bedside: continuous multiorgan variability monitoring in critically ill patients. Primary care as a complex adaptive system.   Researchers in health services research, health policy, and health administration will find in the Handbook of Systems and Complexity in Health a new way of viewing health and illness, and potentially a new way to organize health care delivery.